Erratum: Performance Improvement of RRT∗ Family Algorithms by Limiting Sampling Range in Circular and Spherical Obstacle Environments (Journal of The Korean Society for Aeronautical and Space Sciences 50: 11 (809-817) DOI : 10.5139/JKSAS.2022.50.11.809) Erratum: 샘플링 범위 제한을 이용한 원 및 구 장애물 환경에서의 RRT* 계열 알고리즘 성능 개량 (Journal of The Korean Society for Aeronautical and Space Sciences 50: 11 (809-817) DOI : 10.5139/JKSAS.2022.50.11.809) - Lee, Sangil; Park, Jongho; Lim, Jaesung (Journal of the Korean Society for Aeronautical and Space Sciences, 2022)
In this article the acknowledgment is missing. It should be read: (No. 2021R1G1A1003429).